An Online Business Model For Export Management Company - Subramanian, Arikrishnan (2000)
The result of this study indicate that search engine list and number of hits, E-mail marketing and number of hits are dependent each other. A successful business model must able to pull repeated customer via-email and search engine. On the other hand, there is sufficient proof to conclude that number of business enquiries increased upon implementation of online Global Business Exchange model.